Effect of the probiotic strain, Lactiplantibacillus plantarum P9, on chronic constipation: A randomized, double-blind, placebo-controlled study - Teng Ma; Ni Yang; Yong Xie; Yingmeng Li; Qiuping Xiao; Qiong Li; Hao Jin; Longjin Zheng; Zhihong Sun; Kexuan Zuo; Lai-Yu Kwok; Heping Zhang; et al. (Elsevier, 2023)
Chronic constipation (CC) is a common gastrointestinal condition associated with intestinal inflammation, and the condition considerably impairs patients' quality of life. We conducted a large-scale 42-day randomized, double-blind, placebo-controlled trial to investigate the effect of probiotics in alleviating CC. 163 patients diagnosed with CC (following Rome IV criteria) were randomly divided into probiotic (n = 78; received Lactiplantibacillus plantarum P9 [P9]; 1 ×1011 CFU/day) and placebo (n = 85; received placebo material) groups. Ingesting P9 significantly improved the weekly mean frequency of complete spontaneous bowel movements (CSBMs) and spontaneous bowel movements (SBMs), while significantly reducing the level of worries and concerns (WO; P < 0.05). Comparing with the placebo group, P9 group was significantly enriched in potentially beneficial bacteria (Lactiplantibacillus plantarum and Ruminococcus_B gnavus), while depriving of several bacterial and phage taxa (Oscillospiraceae sp., Lachnospiraceae sp., and Herelleviridae; P < 0.05). Interesting significant correlations were also observed between some clinical parameters and subjects' gut microbiome, including: negative correlation between Oscillospiraceae sp. and SBMs; positive correlation between WO and Oscillospiraceae sp., Lachnospiraceae sp. Additionally, P9 group had significantly (P < 0.05) more predicted gut microbial bioactive potential involved in the metabolism of amino acids (L-asparagine, L-pipecolinic acid), short-/medium-chain fatty acids (valeric acid and caprylic acid). Furthermore, several metabolites (p-cresol, methylamine, trimethylamine) related to the intestinal barrier and transit decreased significantly after P9 administration (P < 0.05). In short, the constipation relief effect of P9 intervention was accompanied by desirable changes in the fecal metagenome and metabolome. Our findings support the notion of applying probiotics in managing CC.